Crystallization-free and low-cost deep eutectic solvents for absorption thermal battery utilizing ultra-low-grade energy. (15th May 2023) - Sui, Yunren; Ding, Zhixiong; Zhai, Chong; Lin, Haosheng; Wu, Wei
Highlights: Crystallization-free and low-cost deep eutectic solvents are investigated for energy storage. NH3 /Glyceline is the most energy-efficient at low generation/evaporation temperatures. The minimal charging temperature with auxiliary compression is reduced to as low as 40 °C. NH3 /Glyceline can operate at lower charging/discharging temperatures than H2 O/LiBr. NH3 /Glyceline significantly slashes the system cost by 41.89 %. Abstract: Absorption thermal batteries (ATBs) play a significant role in balancing the mismatch between ultra-low-grade renewable/waste energy supply and building energy demand. Working fluids are critical to the high performance and reliability of ATBs, but conventional salt-based mixtures suffer from crystallization risks, while the popular ionic liquid-based mixtures are quite expensive. Therefore, crystallization-free and low-cost deep eutectic solvents (DESs) are proposed to achieve reliable and affordable ATBs. The property estimation based on the NRTL model and the cycle model based on mass and energy conservation are established and verified with high accuracies, which are used to investigate the energy storage performance of five H2 O/DESs and four NH3 /DESs. A comprehensive comparison between the emerging DES-based and traditional working fluids from multifaceted viewpoints (efficiency, compactness, exergy, response rate, applicability, heat transfer, reliability, and economics) is conducted. For a basic ATB with inferior operating conditions (generation temperature < 72 °C, evaporation temperature < 1 °C, or absorption temperature > 40 °C), NH3 /Glyceline yields the highest energy storage efficiency (ESE) and exergy efficiency (EXE), outperforming the traditional refrigerant/salts. A compression-assisted ATB is further adopted, enabling NH3 /DESs to utilize ultra-low-grade heat as low as 40 °C. NH3 /Glyceline yields the highest ESE of 0.752 and EXE of 0.599 at a generation temperature of 50 °C. It also exhibits a rapid response rate with the highest maximum vapor mass flow rate of 5.4 g/s and the shortest discharging time (73.22 min). NH3 /Glyceline exhibits the widest applicability, with an applicable operating range ratio of 87.72%, much higher than that of H2 O/LiBr (23.72%). The compression-assisted ATB using NH3 /Glyceline is the most promising for large-scale applications owing to the lowest levelized cooling capacity cost of 0.239 $/kWh, which is 41.89% lower than that of H2 O/LiBr and 96.58% lower than that of H2 O/[EMIM][OAc].